Social Construction and Millennial Habituation of Sunan GunungJati's Tomb in Astana Village, Cirebon - Safrudin, Safrudin; Pramono, Suwito Eko; Hardati, Puji (Universitas Negeri Semarang, 2024)
The existence of Sunan Gunung Jati Tomb in Astana Village, Cirebon Regency, has become an important pilgrimage center that provides economic opportunities for the local community. This study aims to examine the social construction and habituation of the millennial generation regarding the tomb, as well as its utilization to increase community income. A qualitative approach with phenomenological methods was used to understand the millennial generation's behavior, perceptions, and interactions with local cultural traditions. Data were obtained through observations, interviews, and document studies. The results showed that the millennial generation has a high awareness of the importance of maintaining cultural traditions, which is reflected in their active involvement in traditional activities. However, the utilization of tombs to increase income is still not optimal, with the main focus on economic aspects rather than cultural preservation. Technology, particularly social media, plays an important role in promoting and maintaining cultural awareness. The findings provide guidance for village governments and related institutions to develop programs that support local cultural preservation through collaboration, education and wise use of technology.